Short- and long-term outcomes after surgical treatment of 5918 patients with splenic flexure colon cancer by extended right colectomy, segmental colectomy and left colectomy: a systematic review and meta-analysis - Cao, Yu; He, Mingze; Chen, Kuo; Liu, Zheng; Khlusov, Denis I.; Khorobrykh, Tatyana V.; Cao, Xinren; Panova, Polina D.; Efetov, Sergey K.; Kazaryan, Airazat M. (Frontiers in Oncology, 2024)
Background Colorectal cancer is among the most common cancers in the world, and splenic flexure colon cancer accounts for about 2-5% of them. There is still no consensus on the surgical treatment of splenic flexure colon cancer (SFCC), and the extent of surgical resection and lymph node dissection for SFCC is still controversial. Aim To compare the postoperative and long-term oncologic outcomes of extended right colectomy (ERC), segmental colectomy (SC) and left colectomy (LC) for SFCC. Method Up to March 2024, retrospective and prospective studies of ERC, SC, and LC for SFCC were searched through databases. Pooled weighted/standardized mean difference (WMD/SMD), odds ratio (OR) and hazard ratio (HR) with 95% confidence interval (CI) were calculated using a fixed effects model or random effects model, and meta-analysis was performed using Stata. Results This meta-analysis includes 5,918 patients from 13 studies with more lymph node harvest (OR:6.29; 95%Cl: 3.66-8.91; Z=4.69, P=0), more operation time (WMD: 22.53; 95%Cl: 18.75-26.31; Z=11.68, P=0), more blood loss (WMD:58.44; 95%Cl: 20.20-96.68; Z=2.99, P=0.003), longer hospital stay (WMD:1.74; 95%Cl: 0.20-3.29; Z=2.21, P=0.03), longer time to return to regular diet (WMD:3.17; 95%Cl: 2.05-4.30; Z=5.53, P=0), longer first flatus time (WMD:1.66; 95%Cl: 0.96-2.37; Z=4.61, P=0) in ERC versus SC. More lymph node harvest (WMD: 3.52; 95% Cl: 1.59-5.44; Z=3.58, P=0) in ERC versus LC and LC versus SC (WMD: 1.97; 95% CI: 0.53-3.41; Z=2.68, P=0.007), respectively. There is no significant difference between anastomotic leakage, postoperative ileus, total postoperative complication, severe postoperative complication, wound infection, reoperations, R0 resection, postoperative mortality, 5-year overall survival (OS), 5-year disease-free survival (DFS) in three group of patients. In LC versus SC and ERC versus LC, there is no difference between operation time, blood loss, hospital stay, return to regular diet, and first flatus. Conclusion In the included studies, SC and LC may be more advantageous, with fewer postoperative complications and faster recovery. ERC harvests more lymph nodes, but there is no significant difference in long-term OS and DFS between the three surgical approaches. Given that the included studies were retrospective, more randomized controlled trials are needed to validate this conclusion.